Linguistics Characteristics of Social Network - Majeed Mohamed Fareed Majeed; Abdurahman Adisaputera (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
In this paper we introduce the idea of an author about the use of slang language for the period of (16th -20th) century, while other give the use of slang language in the social network and the purpose of the said and the name giving to it. Also the factors that affect the variety of language which will reflect also on the language used in the internet. Hence a new linguistic expression was rising with the name of internet linguistic. We give also some popular internet slangs and its advantages also the emoticons and its different use between males and fameless and prefer to use the capitalize letters. This study also shows the effect of virtual communication on the individuals. We conclude that analytically the internet slang is a specific variety of language and characteristics according to the kind of output, also commonly used than speech, like feedback, emoticons, multiple conversations, hypertext links, persistence, and multiple authorship. Moreover it challenged the cooperative and politeness principles, relevance theory, humor, economy, and tolerance, it express the social identity, rather than illiteracy or the character limit of message services.